The role of lipophagy in liver cancer: mechanisms and targeted therapeutic interventions - Han, Peiyu; Wang, Han; Chen, Yuyu; Ge, Yuqiu; Xu, Huiting; Ren, Hongbo; Meng, Yiteng (Frontiers in Cell and Developmental Biology, 2025)
Liver cancer, the advanced stage of various chronic liver diseases, has garnered attention due to its high incidence and insidious progression. Lipid droplets (LDs), unique lipid storage organelles in hepatocytes, play a pivotal role in lipid metabolism. Lipophagy, a selective autophagy process initially identified in hepatocytes, regulates lipid homeostasis by selectively degrading LDs. This process offers a novel therapeutic avenue for addressing lipid metabolism disorders in liver cancer. This review highlights the regulatory role of lipophagy in liver cancer progression and its therapeutic potential. It elaborates on the molecular mechanisms underlying lipophagy-mediated LDs degradation and discusses the dual regulatory role of lipophagy in liver cancer. While lipophagy can suppress liver cancer development, under specific conditions, it may promote cancer cell proliferation, inhibit apoptosis, facilitate invasion and metastasis, and contribute to treatment resistance. Consequently, strategies targeting lipophagy for liver cancer prevention and therapy hold significant promise. These include interventions through traditional Chinese and Western medicine, as well as lifestyle modifications. This review evaluates current research, hotspots, and controversies in the field, aiming to provide innovative therapeutic strategies for liver cancer associated with abnormal lipid metabolism.